The response of glyphosate-resistant and glyphosate-susceptible biotypes of annual sowthistle (Sonchus oleraceus) to mungbean density. Issue 6 (3rd September 2019) - Mobli, Ahmadreza; Matloob, Amar; Chauhan, Bhagirath Singh
Abstract: Annual sowthistle ( Sonchus oleraceus L.) is a major weed of mungbean crops in Australia. Resistance in this weed to several herbicide groups is a challenging issue for its management. Hence, cultural weed management strategies, such as increasing the crop competitive ability through increased stand density, should be considered to reduce reliance on herbicides. It was hypothesized that a competitive crop stand may reduce the growth and seed production of S. oleraceus . Two pot studies were conducted, and each study was repeated once. The first study evaluated the effect of different mungbean [ Vigna radiata (L.) R. Wilczek] densities (0, 82, 164, 246, and 328 plants m −2 ) on S. oleraceus growth and seed production, while the second study focused on glyphosate-resistant and glyphosate-susceptible biotypes of this weed in competition with densities of 0, 82, and 164 mungbean plants m −2 . Although increasing mungbean density from 0 to 82 and 164 plants m −2 reduced S. oleraceus seed production by 55% and 78%, respectively, a large number of seeds were produced, even at the mungbean density of 328 plants m −2 (1, 185 seeds plant −1 ). Both glyphosate-resistant and glyphosate-susceptible biotypes of S. oleraceus responded similarly to the increase in mungbean density. The results of the second study showed that height, leaves, number of inflorescence, and seed production per plant of both glyphosate-resistant and glyphosate-susceptible biotypes were reduced but not suppressed adequately. The glyphosate-resistant biotype produced fewer leaves and less biomass and, consequently, its seed production was 24% less compared with the glyphosate-susceptible biotype in the no-competition treatment. Both biotypes of S. oleraceus produced about 4, 000 seeds plant −1 in competition with 164 mungbean plants m −2 . The results suggest that crop competition alone cannot provide satisfactory control of S. oleraceus ; therefore, for effective and adequate weed management, other practices such as PRE herbicides should be integrated with increased crop density.